PENGELOLAAN KEUANGAN YANG EFEKTIF MELALUI BEDAH BUKU MANAJEMEN KEUANGAN DAN PERBANKAN MELALUI ZOOM MEETING - Harsono, Pramudi; Triana, Leni; Yuliah, Yuliah; Khaeruman, Khaeruman; Lesmana, Ihwan Satria; Salapudin, Salapudin (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
The community service activity with the theme of financial and banking management book review which was carried out via Zoom Meeting on March 28 2024 aims to increase participants' understanding and skills in managing personal and business finances. This event presents experienced speakers who discuss key concepts in financial management, accompanied by question and answer sessions and interactive discussions. Evaluation of the activity showed that participants felt more skilled and confident in managing finances after participating in this event. This activity also proves the effectiveness of online learning in increasing financial literacy, with higher accessibility and engagement. Recommendations for future activities include presenting more practical examples and tools that participants can use independently to deepen their understanding of financial management